Fabrication of polymeric microstructures Harnessing thin-film instabilities and its Application in point-of-care optical sensing - Mishra, Shubham (IIT BHU Varanasi, 2022)
Abstract is available in the content
Keywords: Fabrication of polymeric microstructures; Harnessing thin-film instabilities; and its Application in point-of-care optical sensing